Creative thinking ability to solve open-ended problems in Madrasah Aliyah - Indriyani, Wiwin Isti; Sutama; Novitasari, Meggy; Alrajafi, Gali; Desmayanasari, Dwi; Adnan, Mazlini (AIP conference proceedings, 2023)
Creative thinking ability is a problem-solving skill that produces a lot of answers and solutions, also create new and different things through idea or work. Observing and developing students’ creative thinking abilities can be done by providing open-ended-based problems. This research was aimed to: 1) describe students’ creative thinking abilities in the aspect of originality, and 2) describe students’ creative thinking abilities in the aspect of elaboration. This type of research was qualitative-ethnographic. In collecting the data, the researchers used student learning outcomes documents and interviews. The subjects of this research were teachers of mathematics and students of class X at Madrasah Aliyah. The researchers used triangulation techniques to test the validity of the data. As for the technique of data analysis, this research used an inductive approach through data reduction, displaying data, and drawing conclusions. From the data, the researchers found: 1) student completions met the aspect of originality by producing a different answer than usual, it showed that students completed SPLTV tasks using an unusual method, namely the matrix method which was more simple and practical, and 2) student completions met the aspect of elaboration by answering meticulously, which meant students understood the context of SPLTV task, did the task in detail, concluded it precisely and clearly.